The Impact of Organoid to Assembloid Technology in Biomedical Research - Meiliana, Anna; Chouw, Angliana; Askandar, Retina Shyallala; Woran, Blessari Tesalonika; Latarissa, Irma Rahayu; Wijaya, Andi (The Indonesian Biomedical Journal, 2026)
Organoids, three-dimensional, self-organized structures derived from pluripotent or adult stem cells, have revolutionized biomedical research by overcoming the inherent limitations of traditional 2D cultures and animal models. This review traces the evolution of organoid technology from initial studies to the contemporary "assembloid" phase, examining systemic inter-organ communication. The primary discovery of this review resides in the shift from descriptive modelling to a functional "Comparative Paradigm." A major perspective addressed is the transition from exclusively descriptive modelling to a functional 'Comparative Paradigm.' By merging developmental biology with bioengineering, a systematic framework is created to discover the most clinically relevant models, employing patient-derived 'avatars' to enhance personalized medicine and and high-throughput drug discovery. Ultimately, this review provides a systematic framework for identifying the most clinically applicable models by integrating developmental biology and bioengineering. The lack of vascularization, embryonic immaturity, and batch-to-batch repeatability issues remain major technical obstacles despite their potential. Finally, we explore potential future approaches in bioengineering, including the incorporation of 3D bioprinting, AI-driven imaging, and microfluidics (organ-on-a-chip). Organoid technology is a key component of next-generation medicine because it bridges the gap between "bench and bedside," providing previously unattainable insights into human biology and illness.KEYWORDS: organoids, stem cells, disease modeling, bioengineering, personalized medicine, assembloids, regenerative medicine; organ-on-a-chip, translational manufacturing